Rancangan Kolam Pengendapan pada PT. Ceria Nugraha Indotama (CNI) - Hasriani Hasriani; Sahrul Poalahi Salu; Nurfasiha (UPT Publikasi Ilmiah Unisba, 2025)
Abstract. A sedimentation pond is an essential component of mine water management designed. At PT Ceria Nugraha Indotama, particularly in the Pit Diamond area, the existing sedimentation pond is unable to accommodate the incoming flow, resulting in frequent overflow. This condition increases the risk of sediment-loaded water being released into the surrounding environment and reduces the overall effectiveness of the mine water management system. This study aims to design an improved sedimentation pond capable of managing sediment more efficiently by considering the hydrological characteristics of the catchment area. The methodology includes analyzing rainfall data, catchment area size, topography, and runoff discharge using several approaches: the Hassing method for determining runoff coefficients, the Gumbel distribution for peak discharge estimation, the Mononobe method for rainfall intensity calculation, the Rational method for runoff determination, and dimension ratio analysis for establishing appropriate pond proportions. Site selection is based on topographic conditions, prioritizing the lowest contour to ensure optimal flow accumulation from the mine opening area. Based on a ten-year rainfall record, the calculated runoff discharge is 5.98 m³/s with a particle settling velocity of 0.00035 m/s. The designed sedimentation pond requires a length of 219 meters, a width of 73 meters, and a depth of 5 meters, providing a total storage capacity of 79,935 m³. The proposed design is expected to enhance sediment removal efficiency prior to discharge and improve the overall performance of mine water management at PT Ceria Nugraha Indotama. Abstrak. Kolam pengendapan merupakan salah satu fasilitas pengelolaan air buangan tambang. Pada PT Ceria Nugraha Indotama, khususnya di area Pit Diamond, kolam pengendapan eksisting tidak mampu menampung volume aliran masuk sehingga sering mengalami limpasan. Kondisi ini berpotensi meningkatkan beban sedimen ke badan air dan menurunkan kinerja pengelolaan air tambang. Penelitian ini bertujuan untuk merancang kolam pengendapan yang mampu mengelola sedimen secara lebih efisien dengan mempertimbangkan karakteristik hidrologi daerah tangkapan. Metode penelitian meliputi analisis data curah hujan, luas daerah tangkapan, dan topografi, serta perhitungan debit limpasan menggunakan analisis hidrologi. Pemilihan lokasi kolam dilakukan berdasarkan kondisi topografi, dengan prioritas pada kontur terendah agar seluruh aliran permukaan dari area bukaan tambang dapat terakumulasi secara optimal. Berdasarkan data curah hujan sepuluh tahun terakhir, diperoleh debit limpasan sebesar 5,98 m³/s dengan kecepatan pengendapan partikel sebesar 0,00035 m/s. Dari hasil perancangan, kolam pengendapan yang dibutuhkan memiliki panjang 219 meter, lebar 73 meter, dan kedalaman 5 meter, dengan kapasitas tampung total 79.935 m³. Rancangan ini diharapkan mampu meningkatkan efektivitas penurunan sedimen sebelum air dibuang ke lingkungan serta memperbaiki kinerja sistem pengelolaan air tambang di PT Ceria Nugraha Indotama.